A estética no pensamento filosófico Degianni Vattimo: o caso da arte e imagens artísticas em meio digital - SILVA, Jocilene Mary Furtado Lima da (2025)
This master's thesis focuses on aesthetics in the philosophical thought of Gianni Vattimo, aiming to explain artistic production in postmodernity. The theoretically grounded research is based on the theories, concepts, and ideas of Vattimian aesthetics, identifying its main theses in order to answer the question of how to analyze artistic productions in postmodernity, more specifically images in digital media, such as works produced and made available in the context of the covid-19 pandemic. To this purpose, a review of previously published literature was conducted, encompassing the works of the Italian philosopher and theorists who underpin his thought. The aesthetic antecedents of Vattimo's philosophical thought were identified, starting from the theory of formativity of his mentor Luigi Pareyson and the concept of production in Aristotle, as analyzed by the Italian philosopher. Next, Vattimo's investigation into the relationship between art and ontology, based on Heideggerian philosophy, was addressed, highlighting the ontological discussion within the aesthetic field, with the aim of understanding the characteristics of art and the artwork as an event, an occurrence with its own order of relations, which founds a new world, a new reality. In this conception, reaching truth in art requires a reflection beyond traditional aesthetics, overcoming the view of art as the bearer of a stable or supreme truth to be unveiled. Subsequently, the development of Vattimo's thought relating the philosophies of Nietzsche and Heidegger was explored in order to address a theory concerning the end of the modern era and the aspects that configure the beginning of postmodernity, which includes an analysis of art. At this point, it was demonstrated that the investigation of art in late modernity must consider the weakening of the metaphysical tradition, because the foundational criteria rooted in Western thought are insufficient for understanding the artistic experience in postmodern society. The Hegelian conception of the death of art was also addressed, which Vattimo interprets as the decline of art, resulting from the predominance of mass media and the content they propagate, with a central influence on daily life and lifestyle in postmodernity, characterizing a general aestheticization of existence. Then, Vattimo's conceptions of postmodernity as a society of generalized communication and the problem of art in such a society were analyzed. In the final chapter, Vattimo's aesthetics were systematized, presenting the main conceptions related to artistic experience in postmodernity. Next, the general aspects of the covid-19 pandemic were described, including an approach to The Covid Art Museum, a virtual Instagram museum with images produced during the global health crisis. Finally, six visual works from the aforementioned museum were analyzed, based on Vattimo's aesthetics, resulting in the main conclusion of the research: Vattimo's philosophical aesthetics is a way of explaining artistic production in postmodernity, not only in general terms, but also enabling the examination of artistic works, as demonstrated in this dissertation.